2014
DOI: 10.2147/dddt.s52354
|View full text |Cite
|
Sign up to set email alerts
|

Genistein suppresses tumor necrosis factor α-induced inflammation via modulating reactive oxygen species/Akt/nuclear factor ΚB and adenosine monophosphate-activated protein kinase signal pathways in human synoviocyte MH7A cells

Abstract: AimsGenistein, an isoflavone derivative found in soy, is known as a promising treatment for rheumatoid arthritis (RA). However, the detailed molecular mechanism of genistein in suppression of proinflammatory cytokine production remains ambiguous. The aim of this work was to evaluate the signal pathway by which genistein modulates inflammatory cytokine expression.Materials and methodsMH7A cells were stimulated with tumor necrosis factor (TNF)-α and incubated with genistein, and interleukin (IL)-1β, IL-6, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 34 publications
3
55
1
Order By: Relevance
“…The mechanisms underlying these effects are not fully understood, and further investigations are needed to explore the detailed molecular mechanism regulated by phytoestrogens. Genistein significantly reduced inflammatory mediators, such as IL-1β, IL-6 and IL-8 production, in TNF-α-activated MH7A cells in vitro [12]. The anti-inflammatory properties of genistein are mediated by the interruption of the ROS/Akt/NF-κB signaling pathway in MH7A cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The mechanisms underlying these effects are not fully understood, and further investigations are needed to explore the detailed molecular mechanism regulated by phytoestrogens. Genistein significantly reduced inflammatory mediators, such as IL-1β, IL-6 and IL-8 production, in TNF-α-activated MH7A cells in vitro [12]. The anti-inflammatory properties of genistein are mediated by the interruption of the ROS/Akt/NF-κB signaling pathway in MH7A cells.…”
Section: Discussionmentioning
confidence: 82%
“…The anti-inflammatory properties of genistein are mediated by the interruption of the ROS/Akt/NF-κB signaling pathway in MH7A cells. These signaling led to a marked decrease of TNF-α-induced pro-inflammatory cytokine production [12].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that ROS can mediate the TNF-α-induced inflammation through the Akt-mediated activation of NF-κB in MH7A cells [28]. To determine whether ROS is involved in the antiinflammation effect, we investigated the potential role of ROS.…”
Section: Cue-induced Ros Formation In Mh7a Cellsmentioning
confidence: 99%
“…Hematopoietic cells are recovered due to enhanced activity of IL-6 and G-CSF level and suppression of TNF-α mediated inflammation through inhibition of ROS/Akt/NF-κB pathway by administration of genistein 24 h prior to radiation exposure. Nanoparticle formulation of genistein shows protection from apoptosis in hematopoietic stem and progenitor cells against radiation and increased bone marrow cellularity that promotes hematopoiesis 32,33 .…”
Section: Genisteinmentioning
confidence: 99%